BETWEEN ANONYMITY AND AUTHORITY: RETHINKING AUTHORSHIP AND POWER IN THE HELP - Savira Martariza Aldya Kautzar; Cynthia Lailanisa Soegiono (Srawung: Journal of Social Sciences and Humanities, 2025)
This study examines the dynamics of authorship, anonymity, and power in Kathryn Stockett’s The Help (2009) and its 2011 film adaptation through the theoretical frameworks of Roland Barthes and Michel Foucault. Employing qualitative textual analysis, the research explores how authorial identity operates within narratives of racial oppression and how anonymity functions simultaneously as a form of protection and erasure. The findings reveal that while Barthes’ notion of the “death of the author” appears to liberate interpretive authority from the creator, Foucault’s concept of the author-function persists as a regulatory mechanism that governs discourse, authorship, and social recognition. In both novel and film, collective authorship emerges as an ideal yet remains undermined by structural hierarchies that privilege white voices. The adaptation’s shift in narrative perspective further demonstrates how medium and ideology shape the representation of authorship. Ultimately, the study concludes that authorship in The Help cannot be separated from power relations and continues to reflect broader questions of voice, legitimacy, and social inequality.